A case of retinoblastoma resulting in phthisis bulbi after proton beam radiation therapy - Norihiko Nakagawa; Takeshi Morimoto; Takako Miyamura; Shigenobu Suzuki; Hiroshi Shimojo; Kohji Nishida (American Journal of Ophthalmology Case Reports, 2022)
Purpose: Proton beam radiation therapy (PBRT) is a treatment option for advanced retinoblastoma (RB) resistant to chemotherapy and focal ophthalmic treatment. Here we report a case of RB with phthisis bulbi following PBRT. Observations: A 16-day-old boy with a family history of RB was referred to our institution. Initial examination revealed an extensive white mass in the right eye and a small tumor near the optic disk of the left eye. The patient was diagnosed with bilateral RB and treated with chemotherapy and focal ophthalmic therapy. The right eye showed shrinkage in the treatment course. The tumor control was not achieved bilaterally, and, therefore, PBRT was performed to preserve the eyes. However, the right eye became significantly phthisical following PBRT and ultimately required enucleation. Conclusions and importance: PBRT for RB may result in phthisis bulbi. Further investigations of its role and possible complications are warranted.